Using technology to provide individualized respite for caregivers in rural communities - Weiss, Linda; Battaglia, Ann; Daniel, Sheaba; Conti, Ashley; Jasani, Foram; Tyler, John (Frontiers in Health Services, 2025)
IntroductionCaregiving for older adults—by family and friends—is an essential component of the U.S. health and long-term care systems. Though often rewarding, caregiving is associated with higher rates of poor health. Respite is valued by caregivers and associated with positive outcomes; however, access is limited. Exhale—The Family Caregiver Initiative, known as Exhale, was established to support the development of respite programming consistent with local priorities.MethodsExhale respite programs participate in an evaluation, which includes caregiver assessments. This paper focuses on results from one Exhale-supported program, Caregiver Tech Solutions (CTS). CTS provides digital technology and coaching to caregivers in rural New York, offering an alternative to place-based respite and allowing caregivers to achieve short breaks from tasks or worries within their homes, on their terms.ResultsEvaluation findings show that most CTS caregivers were children of the care recipients and cared for someone age 75+. Most had not participated in a respite program previously. Significant increases in respite were reported at follow-up: 25% of participants reported respite “every day or almost every day” at follow-up, compared to 12% at baseline. There were also significant declines in caregiver burden.ConclusionsCTS is not unique in use of electronic resources; however, literature remains sparse. Furthermore, pairing technology with coaching is uncommon. Finally, the outcomes demonstrated by CTS counter perceptions that technology-based solutions are not appropriate for older adults or in rural communities. Rather, flexible programs such as CTS represent a promising approach to addressing the needs of rural caregivers.